Effect of Lime and Waste Stone Powder Variation On the pH Values, Moisture Content and Dry Density of Clayey Soil - Armin Roohbakhshan; Behzad Kalantari (International Journal of Advances in Applied Sciences, 2014)
This paper reports an investigation of the influence of waste stone powder and lime on the geotechnical properties of clayey soil. The compaction and changes in the chemical properties of the soil with pH test when mixed with varying proportions of waste stone powder and lime were investigated. Thus, the effectiveness of using Waste Stone Powder (WSP) and lime for preliminary laboratory tests including grain size analysis, PH test and standard Proctor compaction tests for stabilizing fine-grained clayey soil (CL) was investigated in the laboratory. The percentage of lime and WSP used on the samples varied from 0 to 11%, which treatment of the samples with lime and WSP content show that the optimal moisture and maximum dry density values of the samples were changed. The results show increasing in the pH value of clayey soil with increasing amount of waste stone powder and lime. And the optimal moisture content increased with increasing lime and WSP content for all the samples. Also the maximum dry density decreased with increasing lime, whereas the maximum dry density increased with increasing WSP content. The behavior of the geotechnical properties of the clayey soil when blended with waste stone powder and lime indicates that these materials are a good modifier for this soil.